Effectiveness of BPHTB Administration Services at the Makassar City Regional Revenue Agency - Risma Niswaty; Seha Seha; Sitti Hardiyanti Arhas; Muh Nasrullah; Muh Darwis (Universitas Negeri Makassar, 2020)
Administrative services by Fees for Acquisition of Land and Building Rights at the Makassar City Regional Revenue Agency office have resulted in a good performance. The purpose of this research is to describe the effectiveness of administrative services of acquisition duties on land and building rights at the Makassar City Regional Revenue Agency office. This research is a quantitative descriptive. The results showed: shows that the effectiveness of administrative services for land and building rights in the office of the Regional Revenue Agency of Makassar City with the effective category of timeliness which is categorized as effective is 94.61%, the accuracy of services categorized as effective is 71.38%, politeness and friendly categorized as effective 94%, ease of getting services that were categorized as effective 94.46%, and comfort in getting services that were categorized as quite effective 54.30%. This proves that the administrative service of acquisition fees on land and building rights (BPHTB) at the Makassar City Regional Revenue Agency office has been able to carry out its duties and responsibilities and can implement an administrative service system properly.